ETIKA PEMBELAJARAN DALAM PERSPEKTIF KH. HASYIM ASY'ARI - Juhri Jaelani (Taklim : Jurnal Pendidikan Agama Islam, 2021)
AbstractLearning is an obligation (fardu a'in) for Muslims. And learning itself can be obtained through education. In the midst of this digital and instantaneous life, education has an important role in directing the life of the nation and state. Education must not only produce an individual mentality, but must produce good character and ethics. Meanwhile, in an Islamic perspective, education is oriented towards students who have personalities in accordance with Islamic teachings. To achieve the goals of Islamic education, students are required to have ethics as a vehicle for obtaining useful knowledge in living their lives. And also successful learning cannot be separated from the role of an educator who is competent in his field and has a noble personality. Because one of the requirements for the delivery of knowledge is the guidance of a teacher or murshid. In connection with the ethics of students in obtaining knowledge and abilities, and ethics of educators in conveying their knowledge, KH. Hasyim Asy'ari gave various suggestions and advice as provisions for students and educators in carrying out teaching and learning activities.Keywords: Ethics, Learning, KH. Hashim Asy'ari. AbstrakBelajar merupakan suatu kewajiban (fardu a’in) bagi umat Islam. Dan belajar itu sendiri bisa didapatkan melalui pendidikan. Di tengah kehidupan yang serba digital dan instan ini, pendidikan memiliki peranan penting dalam mengarahkan kehidupan berbangsa dan bernegara. Pendidikan tidak hanya harus menghasilkan mentalitas individu saja, akan tetapi harus menghasilkan karakter dan etika yang baik. Sementara dalam perspektif Islam, pendidikan di orientasikan untuk menjadikan peserta didik yang memiliki kepribadian sesuai dengan ajaran Islam. Untuk mencapai tujuan pendidikan Islam tersebut, peserta didik dituntut memiliki etika sebagai wahana dalam memperoleh pengetahuan yang bermanfaat dalam menjalani kehidupannya. Dan juga pembelajaran yang berhasil itu tidak lepas dari peran seorang pendidik yang memiliki kompeten di bidangnya dan memiliki kepribadian yang luhur. Karena di antara syarat tersampaikannya ilmu adalah dengan petunjuk seorang guru atau mursyid. Berkaitan dengan etika peserta didik dalam memperoleh pengetahuan dan kemampuannya, dan etika pendidik dalam menyampaikan ilmunya, KH. Hasyim Asy’ari memberikan berbagai anjuran dan nasihat sebagai bekal bagai peserta didik dan pendidik dalam melakukan aktivitas belajar dan mengajar.Kata kunci: Etika, pembelajaran, KH. Hasyim Asy’ari.